Pharmacokinetic of two oral doses of a 1:20 THC:CBD cannabis herbal extract in cats - Lyons, Chloe; McEwan, Katelyn; Munn-Patterson, Meara; Vuong, Stephanie; Alcorn, Jane; Chicoine, Alan (Frontiers in Veterinary Science, 2024)
Objective: To determine the pharmacokinetics (PK) of two oral doses of a Cannabis herbal extract (CHE) containing 1:20 THC:CBD in 12 healthy Domestic Shorthair cats.Methods: Single-dose PK were assessed after oral administration of CHE at low or high dose (2 mg CBD + 0.1 mg THC, or 5 mg CBD + 0.25 mg THC per kg bw, respectively; n=6 per group) in fasting cats. Blood samples were drawn up to 48 hours following CHE administration. Plasma samples were analyzed for CBD, THC, and metabolites 6-OH-CBD, 7-OH-CBD, 11-OH-THC, and THC-COOH using a previously validated LC-MS/MS method.Results: CBD and THC were quickly absorbed (mean Tmax of 2.4 -2.9 h). Maximum plasma concentrations (Cmax) ranged from 36 -511 ng/mL and 6.8 -61 ng/mL for CBD and THC, respectively. Elimination was initially rapid for both CBD and THC, though a prolonged elimination phase was noted for CBD in some cats (T1/2 λ up to 26 h ). Dose-adjusted Cmax and AUC0-last values were not statistically significantly different (p>0.05) between dose groups indicating CBD and THC concentrations increased in a manner proportional (linear) to the dose. Dose-adjusted THC Cmax and AUC0-last were significantly higher than the corresponding doseadjusted CBD parameters (p < 0.01). Low concentrations of the metabolite 6-OH-CBD were quantified but metabolites 7-OH-CBD, 11-OH-THC, and THC-COOH were not detected in any plasma samples. Inter-individual variance was notable. Salivation shortly after dosing was observed in two cats in the high dose group; these animals had substantially lower cannabinoid concentrations than other cats in this group. No adverse clinical signs (including vomiting, change in mentation or other neurological signs) were noted.Clinical significance: Although cats did not display adverse effects after administration of a single oral dose of 1:20 THC:CBD CHE formulation at 2 or 5 mg CBD/kg bw, observed plasma concentrations were highly variable but generally lower than in dogs receiving the same dose and formulation. Administration of CHE in the fasting state may not optimize CBD absorption, and oral dosing may be challenging when administering an oil-based CHE in some cats.